1995
DOI: 10.1093/chemse/20.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical Localization of Guanylyl Cyclase Activity in Rabbit Taste Bud Cells

Abstract: Guanylyl cyclase activity was cytochemically demonstrated in rabbit foliate taste buds. The enzymatic activity was localized in the apical portion (microvilli and neck) of taste bud cells. Especially strong activity was observed on the microvillous membrane of type I (dark) cells and often on a blunt process of type III cells. The microvilli of type II (light) cells showed weak enzymatic activity. Considering that the apical portion of taste cells is a likely site of interaction between taste stimuli and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…This suggests that c-AMP and IP3 are distributed not only in the papillae but also in the other tissues. It has been reported that guanylyl cyclase activity is localized in the apical portion of taste cells [9]. From the present results, c-GMP mediates sweet taste transduction and IP3 mediates bitter taste transduction, with salt and sour taste transduction possibly being mediated by other system(s).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…This suggests that c-AMP and IP3 are distributed not only in the papillae but also in the other tissues. It has been reported that guanylyl cyclase activity is localized in the apical portion of taste cells [9]. From the present results, c-GMP mediates sweet taste transduction and IP3 mediates bitter taste transduction, with salt and sour taste transduction possibly being mediated by other system(s).…”
supporting
confidence: 62%
“…We found that the concentrations of c-GMP were similar in the tongue and fungiform papillae preparations. This finding suggests that c-GMP is concentrated in the fungiform papillae (taste cell) [9]. The concentrations for c-AMP and IP3 found in the tongue and fungiform papillae preparations were, however, different.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Second, it has been reported that taste buds contain a series of intrinsic molecules participating in the signal transduction cascade involving cyclic nucleotides. These are exemplified by G-protein-coupled receptors (8, 10 -12), gustducin/ transducin (13,14), phosphodiesterase (14,31), adenylyl cyclase/guanylyl cyclase (32,33), and rhodopsin kinase (34). Third, it has been reported that the stimulation of taste cells with some sweet tastants increases their intracellular cAMP level (35).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been reported that taste buds contain a series of intrinsic molecules participating in the signal transduction cascade involving cyclic nucleotides. These are exemplified by G protein‐coupled receptors,3,5‐7 gustducin/transducin,8,9 phosphodiesterase (PDE),9,18 adenylyl cyclase/guanylyl cyclase,19,20 and rhodopsin kinase 21. Third, it has been reported that the stimulation of taste cells with some sweet tastants increases their intracellular cAMP level 22.…”
Section: Discussionmentioning
confidence: 99%